Overcoming Bullying in the Educational Environment: Prevention and Intervention Strategies in Schools - Fauzan, Hilman; Sulaeman, Dedi (Journal of English Language and Education, 2024)
The aim of this study emphasizes on the necessity of a multi-dimensional strategy in combating bullying. The project involves improving teacher training programs, involving stakeholders, and tailoring interventions to the local context. This comprehensive study endeavors to ascertain the extent and ramifications of bullying at SMAN 3 Banjar, in addition to assessing the efficacy of the current anti-bullying initiatives. Methodologically, the research integrates both quantitative and qualitative approaches by descriptive-analytical methods, encompassing extensive surveys, including students, educators, and parents. A meticulous analysis of the gathered data sheds light on various facets: the prevalent forms of bullying, their consequential impact on the affected students, and the perceptions held by key stakeholders regarding both the phenomena of bullying and the preventive measures in place. The findings advocate for the formulation and implementation of more comprehensive, integrated, and context-specific approaches to effectively mitigate and address bullying in educational institutions. Bullying constitutes a critical challenge within educational settings, profoundly influencing students' mental health, academic performance, and overall social welfare. The investigation uncovers a significant occurrence of multiple bullying types—physical, verbal, psychological, and cyber bullying—within the institution. Notably, these acts of bullying have precipitated substantial adverse effects on students' mental health and scholastic achievement, manifesting in forms such as depression, anxiety, and a discernible decline in academic performance. A critical evaluation of the anti-bullying programs implemented reveals notable deficiencies in their execution, resource allocation, and training methodologies, alongside an imperative need for their refinement and contextual adaptation to the specific environment of SMAN 3 Banjar.